The Relationship Between the Level of Public Knowledge and the Use of Mobile JKN Applications in Griya Kalimas Indah Housing, Blitar City - Putri, Fenanda Berliana Putri; Afifah, Lilik; Ikawati, Fita Rusdian; Rusdi, Achmad Jaelani (PROMOTOR, 2025)
Digital transformation is very important in various aspects of life, including the health sector. One of the results of development in the health sector today is the Mobile JKN application. The Mobile JKN application is one of the results of development in the health sector provided by the Ministry of Health through the Health Social Security Administration Agency (BPJS). However, the successful implementation of this application also depends on the level of understanding of users in operating it. So, public knowledge in using it is a factor that needs to be considered. The purpose of this study is to determine the level of public knowledge and identify the use of the Mobile JKN application in Griya Kalimas Indah Housing, Blitar City. The analysis method used is quantitative analytics. The object of the study was 52 respondents from Mobile JKN application users who live in Griya Kalimas Indah Housing, Blitar City. Data collection techniques through filling out questionnaires and observation sheets. The results of this study show that there is a relationship between the level of public knowledge and the use of the Mobile JKN application with the result (P-Value 0.008), the level of knowledge of the people of Griya Kalimas Indah Housing in Blitar City towards the use of the Mobile JKN application is 88.5% well-knowledged. As for the percentage of use of 9.6%, the use is not good. The conclusion is that there is a relationship between the level of public knowledge and the use of the Mobile JKN application in Griya Kalimas Indah Housing, Blitar City.